2008
DOI: 10.1177/1524838008314797
|View full text |Cite
|
Sign up to set email alerts
|

Intersection of Child Abuse and Children's Exposure to Domestic Violence

Abstract: This review addresses research on the overlap in physical child abuse and domestic violence, the prediction of child outcomes, and resilience in children exposed to family violence. The authors explore current findings on the intersection of physical child abuse and domestic violence within the context of other risk factors, including community violence and related family and environmental stressors. Evidence from the studies reviewed suggests considerable overlap, compounding effects, and possible gender diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

37
370
1
13

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 440 publications
(421 citation statements)
references
References 93 publications
37
370
1
13
Order By: Relevance
“…As diversas tipologias de maus-tratos (e.g., Higgins, 2004;McGee & Wolfe, 1991;Wolfe & McGee, 1994) consideram como vítimas tanto os indivíduos a que o abuso é dirigido (por exemplo, a esposa que sofre algum destes tipos de abuso), como crianças e adolescentes que testemunham a situações de abuso (por exemplo, filhos assistirem a violência entre os progenitores; Edwards, Holden, Felitti, & Anda, 2003;Higgins, 2004;Higgins & McCabe, 2000). Assistir a violência de um progenitor ao outro e ser alvo de violência dirigida a si, são fenómenos que aparecem frequentemente associados (Coohey, 2004; T. I. Herrenkohl, Sousa, Tajima, R. C. Herrenkohl, & Moylan, 2008;Kitzmann, Gaylord, Holt, & Kenny, 2003). Assim, grande parte dos estudos com filhos de vítimas de violência doméstica contra mulheres considera a co-ocorrência dos dois tipos de abuso (ser vítima directa de violência e testemunhar violência entre os progenitores, Lepisto, Luukkaala, & Paavilainen, 2011), com o objectivo de garantir maior validade ecológica.…”
Section: Auto-regulação Da Aprendizagem Em Filhos De Vítimas De Violêunclassified
See 1 more Smart Citation
“…As diversas tipologias de maus-tratos (e.g., Higgins, 2004;McGee & Wolfe, 1991;Wolfe & McGee, 1994) consideram como vítimas tanto os indivíduos a que o abuso é dirigido (por exemplo, a esposa que sofre algum destes tipos de abuso), como crianças e adolescentes que testemunham a situações de abuso (por exemplo, filhos assistirem a violência entre os progenitores; Edwards, Holden, Felitti, & Anda, 2003;Higgins, 2004;Higgins & McCabe, 2000). Assistir a violência de um progenitor ao outro e ser alvo de violência dirigida a si, são fenómenos que aparecem frequentemente associados (Coohey, 2004; T. I. Herrenkohl, Sousa, Tajima, R. C. Herrenkohl, & Moylan, 2008;Kitzmann, Gaylord, Holt, & Kenny, 2003). Assim, grande parte dos estudos com filhos de vítimas de violência doméstica contra mulheres considera a co-ocorrência dos dois tipos de abuso (ser vítima directa de violência e testemunhar violência entre os progenitores, Lepisto, Luukkaala, & Paavilainen, 2011), com o objectivo de garantir maior validade ecológica.…”
Section: Auto-regulação Da Aprendizagem Em Filhos De Vítimas De Violêunclassified
“…Como é descrito pelo modelo do perpetrador sequencial, os comportamentos das mulheres vítimas de violência doméstica para com os filhos (nomeadamente as práticas parentais) são significativamente afectados pelo abuso (Coohey, 2004). É frequente que os abusos perpetrados pelo abusador contra a vítima (cônjuge) co-existam em padrões semelhantes de abuso nos filhos (e.g., Coohey, 2004;T. I. Herrenkohl et al, 2008).…”
Section: Auto-regulação Da Aprendizagem Em Filhos De Vítimas De Violêunclassified
“…La situación es aún más grave si tenemos en cuenta que, tal y como señalan numerosas investigaciones, existe una estrecha relación entre la violencia a la pareja y el maltrato infantil en sus diferentes manifestaciones físicas, psicológicas o sexuales, encontrándose esta asociación en entre el 30 y el 60% de los casos (Chang, Theodore, Martin y Runyan, 2008;Edleson, 1999;Goddard y Bedi, 2010;Herrenkohl, Sousa, Tajima, Herrenkohl y Moylan, 2008).…”
Section: Palabras Clave: Violencia Familiar Menores Ajuste Escolarunclassified
“…Although witnessing violence between parents may be considered maltreatment in and of itself (or at least potentially traumatic), literature reviews point to high co-occurrence rates (30%-60%) of documented child maltreatment and IPV (Edleson, 1999). Several factors are associated with the co-occurrence of child abuse and IPV, including lower socioeconomic status, lower parental education levels, unemployment or lower occupational status, substance use in the family, mental illness in caregivers, parenting stress, greater number of children or larger household size, and neighborhood violence (Herrenkohl et al, 2008). One hypothesized mechanism for the link between IPV and child abuse has focused on the perpetrator, if the aggression originates from the same individual.…”
Section: Parental and Familial Contextmentioning
confidence: 99%
“…For example, rigorous research methods are needed to examine whether the vulnerability and protective factors identified in documented abuse reflect actual underlying differences (e.g., between groups) versus biases in the system. Additionally, prevention of maltreatment requires programs to systematically and comprehensively address multiple risk and protective factors, including the family and community (Herrenkohl et at., 2008). While we recommend that future research target multiple levels of influence on maltreatment, so too should policymakers address the implications of multiple system interactions.…”
Section: Recommendations For Policymentioning
confidence: 99%